2019
DOI: 10.21203/rs.2.10850/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ub-clipping: an approach for studying ubiquitin chain architecture

Abstract: The post-translational modification of proteins with ubiquitin is a dynamic multifaceted process affecting all aspects of eukaryotic cellular biology. The complexity of ubiquitin modifications arises from their ability to form architecturally distinct polyubiquitin chains 1-3 . Despite our understanding of the importance of these signals, we currently lack tools and methods to study them. Here we describe an approach, termed Ub-clipping, which provides unprecedented insight into ubiquitin chain architecture. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…Previous work has shown that Parkin is unable to incorporate pSer65-Ub into chains when pSer65-Ub is the only source of Ub. 34,44 Our middle-down data reveal that subunits within a chain are phosphorylated when PINK1 can act on Ub anytime during the chain assembly process. To determine whether phosphorylation occurs on a particular chain type, we performed electron transfer dissociation (ETD) MS/MS analysis on the diGly-pSer65-Ub 1-74 species.…”
Section: Resultsmentioning
confidence: 87%
“…Previous work has shown that Parkin is unable to incorporate pSer65-Ub into chains when pSer65-Ub is the only source of Ub. 34,44 Our middle-down data reveal that subunits within a chain are phosphorylated when PINK1 can act on Ub anytime during the chain assembly process. To determine whether phosphorylation occurs on a particular chain type, we performed electron transfer dissociation (ETD) MS/MS analysis on the diGly-pSer65-Ub 1-74 species.…”
Section: Resultsmentioning
confidence: 87%
“…This will greatly increase the percentage of di-Gly-linked peptides present in the digested sample. Since OtUBD has exceptionally high affinity towards free ubiquitin, it could also be used with the Ub-Clipping technique (77). In Ub-Clipping, ubiquitylated proteins are cleaved at the ubiquitylation sites by the protease Lb-Pro to generate diGly-linked monoubiquitin species and free ubiquitin 1-74 .…”
Section: Discussionmentioning
confidence: 99%